(untitled) (Research, Society and Development, 2020)
The fragmentation in forest ecosystems and the consequent edge effect promote changes in the diversity of organisms in this habitat, including those belonging to the edaphic fauna. Thus, this work aimed to verify the dynamics of litter decomposition in a fragment of Mixed Ombrophilous Forest as well as to characterize the edaphic fauna existing inside and at the edge of the fragment. For this, litter bags and pittfall traps were installed on the edge and inside the fragment to assess the litter mass loss and the soil fauna, respectively. As a result, it was found that the distribution homogeneity was greater at the edge compared to the interior, caused by the great dominance of the groups Diptera and Colembola. The principal component analysis did not indicate edaphic groups directly correlated to any of the study areas. Regarding the litter decomposition rate, it was found that there was no difference between areas. However, in both there was a difference in the speed of decomposition at 30 days compared to 60 and 90 days, which did not differ between them. These results indicate that in the evaluated situation, forest fragmentation did not affect the dynamics of decomposition between the forest’s edge and interior areas.